The skull roof tracks the brain during the evolution and development of reptiles including birds - Fabbri,M; Koch,NM; Pritchard,AC; Hanson,M; Hoffman,E; Bever,GS; Balanoff,AM; Morris,ZS; Field,DJ; Camacho,J; Rowe,TB; Norell,MA; et al. (Nature Ecology and Evolution, 2017)
Major transformations in brain size and proportions, such as the enlargement of the brain during the evolution of birds, are accompanied by profound modifications to the skull roof. However, the hypothesis of concerted evolution of shape between brain and skull roof over major phylogenetic transitions, and in particular of an ontogenetic relationship between specific regions of the brain and the skull roof, has never been formally tested. We performed 3D morphometric analyses to examine the deep history of brain and skull-roof morphology in Reptilia, focusing on changes during the well-documented transition from early reptiles through archosauromorphs, including nonavian dinosaurs, to birds. Non-avialan taxa cluster tightly together in morphospace, whereas Archaeopteryx and crown birds occupy a separate region. There is a one-to-one correspondence between the forebrain and frontal bone and the midbrain and parietal bone. Furthermore, the position of the forebrain–midbrain boundary correlates significantly with the position of the frontoparietal suture across the phylogenetic breadth of Reptilia and during the ontogeny of individual taxa. Conservation of position and identity in the skull roof is apparent, and there is no support for previous hypotheses that the avian parietal is a transformed postparietal. The correlation and apparent developmental link between regions of the brain and bony skull elements are likely to be ancestral to Tetrapoda and may be fundamental to all of Osteichthyes, coeval with the origin of the dermatocranium.